Assessing the impacts of COVID-19 on household incomes and poverty in Rwanda: A microsimulation approach - Diao, Xinshen; Rosenbach, Gracie; Spielman, David J.; Aragie, Emerta A. (International Food Policy Research Institute, 2021)
In Rwanda, as in other countries, different types of households will experience the economic effects of the COVID-19 pandemic differently. We use a microsimulation approach to highlight the importance of these differences and to draw attention to the diversified livelihood strategies of Rwandan households in order to fully understand COVID-19’s impacts on their income and poverty status. Our approach complements macro-level assessments of COVID-19’s economic impacts, focusing on the contribution of the income sources, asset holdings, and location (urban/rural) of households to understanding these differential effects.